(untitled) (Zoological Archives: An International Journal, 2022)
Amphibians exhibit sharper latitudinal and altitudinal gradients in species richness than any other vertebrate class, with diversity peaking in humid tropical lowlands and declining steeply toward temperate zones and montane environments. Understanding the ecological drivers of these patterns – disentangling the relative contributions of energy availability, water balance, habitat heterogeneity, evolutionary history, and human disturbance – is fundamental both to macroecological theory and to predicting how amphibian communities will respond to climate and land-use change. This study analysed the ecological drivers of amphibian species richness across 847 grid cells of 1-degree resolution covering the entire global amphibian distribution, using a hierarchical mixed-effects model framework incorporating 14 ecological predictor variables and controlling for spatial autocorrelation. Mean annual actual evapotranspiration (AET) – a combined measure of energy and water availability – was the single strongest predictor of amphibian richness (partial R2 = 47.4% after controlling for spatial structure; beta = 0.84; p < 0.001), consistent with the energy-water hypothesis. Habitat heterogeneity (terrain ruggedness index; partial R2 = 18.4%) and forest cover (partial R2 = 14.7%) were the second and third strongest predictors respectively. Human footprint index was a significant negative predictor (partial R2 = 12.4%; p < 0.001) after controlling for all other variables, confirming an independent anthropogenic richness deficit beyond habitat loss captured by forest cover alone. Time-since-Pleistocene-glaciation (refugia age) explained 8.4% of residual richness variance after other predictors, providing evidence for a historical legacy of Pleistocene range contractions in temperate zones still detectable in current richness patterns.